2004
DOI: 10.2320/matertrans.45.2686
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystallization and Amorphization Mechanisms in Zr-X Alloys during the ARB Process

Abstract: The gradual nanocrystallization and amorphization mechanisms in various Zr-X alloys during accumulative roll bonding (ARB) are explored. The effects of strain accumulation, the relative initial hardness of the elemental foils, the enhanced diffusion, and the critical nano size for the sudden transformation from the nanocrystalline phase to the amorphous state are examined. For elemental foils with compatible initial hardness, the nanocrystallization and amorphization rates appear to be higher. The estimated di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Within the last two decades, on the other hand, various severe plastic deformation (SPD) processes for achieving grain refinement have been developed [7][8][9]. It was also found that SPD technique can be used to fabricate non-equilibrium alloys or even amorphous alloys [10,11]. High pressure torsion (HPT) is a kind of these SPD techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Within the last two decades, on the other hand, various severe plastic deformation (SPD) processes for achieving grain refinement have been developed [7][8][9]. It was also found that SPD technique can be used to fabricate non-equilibrium alloys or even amorphous alloys [10,11]. High pressure torsion (HPT) is a kind of these SPD techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Future simulation can be conducted for one pureelement nanocrystalline phase in conjunction with fully mixed amorphous matrix, as for the experimentally observed situation. It is expected that the ARB cycles needed to complete the mixing and vitrification may be further reduced to around three cycles, as observed previously in the Zr-Ti system [7,8].…”
Section: Simulated Microstructure Evolution During Arbmentioning
confidence: 66%
“…The nanocrystalline phase near the interface is around 2 nm with nearly sphere in shape and it seems to become unstable when the size is further refined to below 2 nm. Previous studies [6,8] have concluded that the pronounced increase in interfacial energy of the nanocrystalline phase lead to the transformation into the amorphous state, and interdiffusion across the phase boundary is the controlling atomic mechanism [14], as depicted in Fig. 1(b).…”
Section: Transformation Between Nanocrystalline and Amorphous Phasementioning
confidence: 95%
See 2 more Smart Citations